Pemanfaaatan Lahan Sempit Dan Non Produktif Untuk Budidaya Jamur Tiram Pada Kecamatan Boyolangu Kabupaten Tulungagung - Kus Irawan Prabowo (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2021)
The covid-19 virus that spreads in various countries around the world is one of the causes of the decline in the world economy, including Indonesia. This has caused many people in Indonesia an economic decline and even loss of their jobs due to a reduction in the number of workers in companies affected by this pandemic. Therefore, special strategies and solutions are needed to deal with the current economic downturn in society. One of the solutions is through the use of unproductive narrow land for oyster mushroom cultivation. The research objectives are 1) knowing the condition of the unproductive narrow land 2) implementing unproductive narrow land use in oyster mushroom cultivation, and 3) evaluating changes in unproductive narrow land and yields of oyster mushroom cultivation in the society of Boyolangu District, Tulungagung Regency. Qualitative research method with the type of research PAR (Participatory action research). The result of the research is that narrow unproductive land can be used for oyster mushroom cultivation, encourage economic independence by increasing people's income, and open new insights about resilience to pandemic situations, and this can be done by several layers of society both young people and housewives.